2016
DOI: 10.1016/j.jhin.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Early impact of rotavirus vaccination in a large paediatric hospital in the UK

Abstract: The impact of routine rotavirus vaccination on community-acquired (CA) and healthcare-associated (HA) rotavirus gastroenteritis (RVGE) at a large paediatric hospital, UK, was investigated over a 13-year period. A total of 1644 hospitalized children aged 0-15 years tested positive for rotavirus between July 2002 and June 2015. Interrupted time-series analysis demonstrated that, post vaccine introduction (July 2013 to June 2015), CA- and HA-RVGE hospitalizations were 83% [95% confidence interval (CI): 72-90%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
2
20
0
1
Order By: Relevance
“…A recent systematic review has shown a significant impact of RV vaccination on hospitalisation, with reductions in numbers hospitalised of 65–84% across several European countries,5 and similar results have been seen in early UK data 6. However, the impact of the recently introduced RV vaccination in the UK, particularly on hospital inpatient activity and complications of RV infection, has not yet been widely reported.…”
Section: Introductionmentioning
confidence: 71%
“…A recent systematic review has shown a significant impact of RV vaccination on hospitalisation, with reductions in numbers hospitalised of 65–84% across several European countries,5 and similar results have been seen in early UK data 6. However, the impact of the recently introduced RV vaccination in the UK, particularly on hospital inpatient activity and complications of RV infection, has not yet been widely reported.…”
Section: Introductionmentioning
confidence: 71%
“…Rotaviruses are, like noroviruses, agents of gastroenteritis, but the disease is commonly associated with children under the age of 5 where severe diarrhoea and vomiting can lead to over 10,000 hospitalizations per year in England and Wales (50). Since the introduction of the live-attenuated vaccine Rotarix, the incidence of gastroenteritis in England has declined, specifically for children aged <2 and during peak rotavirus seasons (5153). Therefore, the discovery of a diverse assemblage of rotavirus genome segments in the wastewater samples here was less expected than the norovirus discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the rotavirus vaccine, diarrheal disease among children remains a notable burden, especially in low-income countries. The rotavirus vaccine managed to decrease the number of dehydrated children, hospital admissions, calls, and visits owing to AGE caused by rotavirus (21). The live-attenuated oral monovalent rotavirus vaccine was proven to be highly effective, providing 85% protection against severe AGE caused by rotavirus and 100% protection against the most severe episodes of dehydration (21,22).…”
Section: Discussionmentioning
confidence: 99%